Gender impact on the outcome of rehabilitation programs in psychiatry: Brief report from a metropolitan residential rehabilitative service - Cafaro, Rita; Rosti, Chiara Ada Maria; Cerolini, Lucia; Varinelli, Alberto; Charitos, Socrates; Magnotti, Roberta; Benatti, Beatrice; Dell’Osso, Bernardo; Viganò, Caterina A. (Frontiers in Psychiatry, 2023)
BACKGROUND Differences based on gender in the presentation and outcome of many psychiatric conditions have been highlighted in the past years. Moreover, women are often underrepresented in research samples, thus leading to a worse understanding and addressing of their needs. As regards psychiatric rehabilitation, few studies have focused on the influence of gender on the outcomes of rehabilitation programs. OBJECTIVES This study aimed to analyse the impact of gender on socio-demographic and clinical characteristics, as well as on main rehabilitation outcomes, in a sample of subjects undergoing rehabilitation programs in a metropolitan residential service. METHODS We collected socio-demographic and clinical variables and measured rehabilitation outcomes (through specific psychometric scales) of all subjects discharged from the metropolitan residential rehabilitative service of the Luigi Sacco Hospital in Milan, Italy, from January 2015 to December 2021. Gender differences were analysed through t-test and chi-square for continuous and categorical variables respectively. RESULTS In a total sample of 129 subjects equally distributed for gender (50.4% women), all subjects showed a general improvement after their rehabilitation program, based on scores at the psychometric scales used as outcome measures. However, women had a higher proportion of discharges to their own household (52.3% vs. 25% of men). They also showed higher educational status (53.8% completed high school vs. 31.3% of men). Clinically, they showed longer duration of untreated illness (3.6 ± 7.31 vs. 1.06 ± 2.35 years) and lower frequency of substance use disorders compared to men (6.4% vs. 35.9%). CONCLUSIONS The main result of this study shows, in light of an equal improvement in psychopathological and psychosocial functioning after the rehabilitation program, better outcomes in women compared to men, with a higher frequency of return to their own household after the completion of a rehabilitation program compared to men.